Pola Komunikasi Organisasi Pengguna Paperless Office Di Institut Pemerintahan Dalam Negeri: Studi Deskriptif kualitatif Pengguna Paperless Office di IPDN - Trias Pyrenia Iskandar (Ilmu Komunikasi, FISIP Universitas Pasundan, 2020)
ABSTRAC Paperless office (PLO) was first predicted in the June 30 Business Week article in 1975, which says that office automation reduces the overall paper count, especially in routine activities such as data archiving. PLO is a new medium where it has advantages over the old media, which can provide interaction facilities between users that are textual, and visual, and penetrate the boundaries of space and time. The user of the paperless office at the Institute of Government of the Interior is the organization's communication because it binds the organizational unity that is behind the author's curiosity to examine the Paperless Office Pattern Of Communication In Ipdn. The method in this study using descriptive analytics aims to describe and analyze patterns of organizational communication that occurs in applying paperless office The results of this study is that in using paperless office. Communication patterns both from the bottom and bottom and up are not too formal because each user can comment on each other like using social media, in the dissemination of information such as content memo patterned communication Y, Curgas content is patterned circle communication and expression content is stellar patterned communication. However, in using this PLO there are communication barriers such as human resources, leadership, and accostumed in using technology.